A new species of reed snake, Calamaria (Squamata: Colubridae), from the Central Truong Son (Annamite mountain range), Vietnam - Ziegler, Thomas; Quyet, Le Khac (Zootaxa, 2005)
A new species of Calamaria is described from the Truong Son (Annamite mountain range) of Quang Binh province in central Vietnam. The new species is characterized by its dark, iridescent body with four yellowish to beige zigzag shaped bands, light dorsal markings on base and tip of tail, light venter, modified maxillary teeth, large size (455 mm total length), tail tapering gradually to a point, reduction to five dorsal scale rows on tail, 198 ventral scales, 21 divided subcaudals, four supralabials (second and third entering orbit), five infralabials, mental not touching anterior chin shields, three gular scales in midline between posterior chin shields and first ventral, rostral being wider than high, paraparietal being surrounded by six shields and scales, and by the absence of a preocular scale. The new taxon is known only from a single adult female specimen that was collected in a primary limestone forest cave. It is the fifth species of Calamaria recorded from Vietnam.